Tillage rotation and biostimulants can compensate for reduced synthetic agrochemical application in a dryland cropping system - Flackson Tshuma; Pieter Andreas Swanepoel; Johan Labuschagne; James Bennett; Francis Rayns (Cogent Food & Agriculture)
The effects of four continuous tillage regimes; mouldboard ploughing, tine-tillage, shallow tine-tillage, no-tillage; and three tillage rotations (involving shallow tine-tillage once every two, three, and four years in rotation with no-tillage), and two rates of synthetic agrochemicals (standard: with regular application of synthetic agrochemicals; and reduced: fewer synthetic agrochemicals in combination with biostimulants) on wheat and canola yield and quality were investigated between 2018 and 2020 under typical Mediterranean climatic conditions in South Africa. It was hypothesised that a combination of tillage rotations and the application of reduced synthetic agrochemicals will improve crop yield and quality relative to mouldboard ploughing or no-tillage. Results showed that a combination of reduced application of synthetic agrochemicals and tillage rotation practices maintained but did not significantly increase crop yield and quality, relative to no-tillage and mouldboard ploughing. Results also showed that intensive ploughing is unnecessary as it did not significantly increase yields (p > 0.05). In addition, it is possible to reduce the quantity of synthetic agrochemicals applied by partially replacing them with biostimulants without significant changes in grain or seed yields and quality. We, therefore, suggest that producers opt for biostimulants in combination with no-tillage or tillage rotation as a sustainable way of farming.